Pencegahan Penyakit Perilaku Menyimpang Anak Usia Remaja dengan Penerapan Komunikasi dalam Keluarga - Lisa Ernita; Saputra, Rahmat; Andriani, Liza (LPPM Hang Tuah Pekanbaru, 2024)
Background; Deviate behavior is very vulnerable and is often encountered among teenage children. Of course, this is the impact of the imperfect communication and socialization process between teenage children and their closest family environment such as parents. This can only be overcome if the family functions are running well. The purpose of writing this article is to survey several writings related to family communication on behavioral deviations in teenage children, Methodology: Conduct a review of 25 articles selected according to keywords, then the sample in this writing is 15 articles of which 10 are international articles and 5 national articles with quantitative and qualitative research types, Results: From the 15 articles read, the results that cause deviant behavior in children and adolescents are: 1. Lack of communication between teenage children with parents, where parents are the most important and highly expected people in the family to be able to direct and guide a child to face his or her life. 2. The school environment also supports character building, because ≥ 8 hours the child is at school with the teacher as a parent and a trusted person in the school environment. 3. The peer environment that has a great influence invites positive and negative directions. 4. The need for religious education and proper religious understanding to avoid this deviant behavior Conclusion: A holistic, religious, and collaborative approach between teenage children and parents can play a significant role in preventing and overcoming deviant behavior in teenage children.